MAKNA TRADISI MACCELLECCELLENG DALAM PERKAWINAN ADAT BUGIS DI DESA PADANG LAMPE KECAMATAN MA’RANG KABUPATEN PANGKEP - Jalaluddin. B; Citra Ainun; Irnawati Irnawati (SOURCE : Jurnal Ilmu Komunikasi, 2022)
This study emphasizes the activities of the traditional marriage process in the Buginesse community in Padang Lampe Village, Pangkep Regency, and South Sulawesi which still tends to prioritize material values as a necessity. The purpose of this research is to find out the process of Macellengcelleng Tradition and the meaning of this tradition. This research used a qualitative methodology with a symbolic interactional approach. The data findings were analyzed through three stages, namely Data Reduction, Data Presentation, and Conclusion Drawing. The study found two important things, namely (1) this tradition pays great attention to dialogic activities to reach a consensus or agreement. (2) this tradition builds an awareness that the material equipment prepared does not only describe a hedonistic lifestyle, but also perseverance, discipline, gratitude, happiness, prosperity, self-esteem, sustenance, and the responsibility of the prospective husband as head of the household. Thus, this tradition teaches a maturity in behavior and relationships with others that can be seen through the practice of communication and responsibility from a man to the woman he wants to marry. In other words, the local wisdom of Macellengcelleng is a form of civilization that we know as Maturity Value.